An efficient and unique method for the growth of spindle shaped Mg-doped cerium oxide nanorods for photodegradation of p-Nitrophenol. Issue 19 (1st October 2022) - Chahal, Surjeet; Phor, Lakshita; Singh, Saurabh; Singh, Amanvir; Malik, Jaideep; Goel, Pratibha; Kumar, Ashok; Kumar, Suresh; Ankita,; Kumar, Parmod
Abstract: Photocatalytic degradation of phenolic dyes has always been a challenge in front of the research community. Therefore, to resolve the problem, present work aims to synthesize the unique cerium oxide nanorods using modified solvothermal method. These nanorods are combined in such a manner that they form spindle-shaped morphology. X-ray diffraction (XRD) and transmission electron microscopy (TEM) measurements confirmed the formation of spindle-shaped cerium oxide nanorods. Raman and X-ray photoelectron spectroscopy (XPS) are employed to explore the electronic properties, and lattice defects. The unique morphology and lattice defects are responsible for effective p -Nitrophenol (PNP) degradation up to 90.2 % in 5 h using 6 % Mg doped CeO2 photocatalyst in the presence of UV light. The oxygen vacancies in the form of lattice defects increased the magnetization in Mg doped CeO2 that have been explained based on F-center exchange (FCE) mechanism. Hence, Mg doped cerium oxide has been proven as a bi-functional material for spintronics and photocatalysis.